Analysis of anticipatory cues in karate kumite using an in-situ-study - Petri, K.; Droste, M.; Witte, K. (Journal of Martial Arts Research, 2020)
Anticipatory cues, and how they are affected by gender, expertise and age, are not identifiedsufficiently in karate kumite. In an in-situ study, 24 karate athletes reacted to attacks of a realopponent and we analyzed the cues by identification of the first time of the reaction andsubtraction of individual reaction times from that point to examine the relevant movementstage of the attack using video analysis (100 Hz). We divided the attacks into four movementstages. In our sample, we compared men with women and athletes of international withnational competition experience, and we related the age to the relevant movement stage. Wefound that regardless of gender, expertise level or age, the arm attacks Gyaku-Zuki, Gyaku-Zukioverrun and Kizami-Zuki were most often recognized in movement stage 1 (early steps) and 2(reduction of interpersonal distance). These movement stages seem to serve as universal cuesfor all analyzed attack types.